Curcumin Inhibits Prostate Cancer Bone Metastasis by Up-Regulating Bone Morphogenic Protein-7 in Vivo - Dorai, Thambi (2014)
A number of studies have focused on the beneficial properties of Curcumin (diferuloyl methane, used in South Asian cuisine and traditional medicine) such as the chemoprevention of cancer. Recent studies have also indicated that this material has significant benefits for the treatment of cancer and is currently undergoing several clinical trials. We have been interested in the application of this compound as a therapeutic agent for advanced prostate cancer, particularly the skeletal complications in this malignancy. Our earlier work indicated that this compound could inhibit the osteomimetic properties which occur in castration resistant prostate cancer cells, by interfering with the common denominators between these cancer cells and the bone cells in the metastatic tumor microenvironment, namely the osteoblasts and the osteoclast. We predicted that curcumin could break the vicious cycle of reciprocal stimulation that results in uncontrolled osteolysis in the bony matrix. In this work, we have evaluated the potential of this compound in inhibiting the bone metastasis of hormone refractory prostate cancer cells in an established animal model. Our results strongly suggest that curcumin modulates the TGF-β signaling that occurs due to bone matrix degradation by up-regulating the metastasis inhibitory bone morphogenic protein-7 (BMP- 7). This enhancement of BMP-7 in the context of TGF-βin the tumor microenvironment is shown to enhance the mesenchymal-to-epithelial transition. Most importantly, we show that as a result of BMP-7 up-regulation, a novel brown/beige adipogenic differentiation program is also up-regu- lated which plays a role in the inhibition of bone metastasis. Our results suggest that curcumin may subvert the TGF-βsignaling to an alternative adipogenic differentiation program in addition to the previously established interference with the osteomimetic properties, thus inhibiting the bone metastatic processes in a chemopreventive as well as therapeutic setting.